A Chinese Herbal Formula to Improve General Psychological Status in Posttraumatic Stress Disorder: A Randomized Placebo-Controlled Trial on Sichuan Earthquake Survivors. (19th October 2011) - Meng, Xian-Ze; Wu, Feng; Wei, Pin-Kang; Xiu, Li-Juan; Shi, Jun; Pang, Bin; Sun, Da-Zhi; Qin, Zhi-Feng; Huang, Yi; Lao, Lixing
Abstract : Introduction . Posttraumatic stress disorder (PTSD) is accompanied by poor general psychological status (GPS). In the present study, we investigated the effects of a Chinese herbal formula on GPS in earthquake survivors with PTSD. Methods . A randomized, double-blind, placebo-controlled trial compared a Chinese herbal formula, Xiao-Tan-Jie-Yu-Fang (XTJYF), to placebo in 2008 Sichuan earthquake survivors with PTSD. Patients were randomized into XTJYF (n = 123 ) and placebo (n = 122 ) groups. Baseline-to-end-point score changes in the three global indices of the Symptom Checklist-90-Revised (SCL-90-R) and rates of response in the SCL global severity index (GSI) were the primary endpoints. A subanalysis of the nine SCL factors and the sleep quality score were secondary endpoints. Results and Discussion . Compared to placebo, the XTJYF group was significantly improved in all three SCL global indices ( P = 0.001~0.028). More patients in the XTJYF group reported "much improved" than the placebo group ( P = 0.001). The XTJYF group performed significantly better than control in five out of nine SCL factors (somatization, obsessive-compulsive behavior, depression, anxiety, and hostility ( P = 0.001~0.036)), and in sleep quality score (P < 0.001 ). XTJYF produced no serious adverse events. These findings suggest that XTJYF may be an effective and safe treatment option for improving GPS in patients with PTSD.